Construction of universal Laurent and Faber series - D. Mayenberger (Հայաստանի ԳԱԱ)
For a finitely connected domain Ω the paper constructively proves the existence of a function f holomorphic on Ω, wose Laurent series partial sums possess universal approximation properties in ΩC. Existence of functions holomorphic on a Jordan domain G, whose Faber series partial sums possess universal approximation prpperties in Gc is demonstraed. the class of functions with these properties is a Gδ-set and is dense in the space of all functions holomorphic on G.
Keywords: Science; Mathematics